Combinatorial effect of zoledronic acid and irradiation on the prevention of DMBA-induced precancerogenic changes in the mammary tissues of rats - Gurocak, Simay; Karabulut, Aysun Bay; Tuzcu, Mehmet; Şahin, Nurhanurhah; Temelli, Oztun; Ince, Volkan; Şahin, Kazım (Wolters Kluwer Medknow Publications, 2016)
Background: At present, the rates of breast cancer are continuously increasing, with over a million new cases being diagnosed worldwide each year. Hence, the development of new breast cancer chemopreventive drugs with acceptable efficacy and toxicity that are suitable for use for a protracted period of time is urgently needed. The present study investigated the potential preventive effects of zoledronic acid [ZOL] and radiotherapy [RT], both alone and in combination, on precancerogenic changes on the breast tissues of females. Materials and Methods: Wistar rats were treated with 7,12-dimethylbenz [a] anthracene [DMBA] at the acute phase. Fifty female rats were divided into seven groups: Control group [I]; ZOL, group [II]; RT, group [III]; DMBA, group [IV]; DMBA + RT, group [V]; DMBA + ZOL, group [VI]; and DMBA + ZOL + RT, group [VII]. Results: The treatment of DMBA-exposed rats with ZOL and RT, both alone and in combination, successfully upregulates the transcriptional levels of Bax, caspase-3, caspase-9, p21, and BRCA 1 in mammary tissues, which may account for the elevated apoptotic activities observed and the eventual inhibition of tumor growth. The administration of RT and ZOL both alone and in combination was found to be effective for inhibiting the DMBA-induced precancerogenic changes on breast tissues and modulating the expression of apoptosis-associated proteins in the acute phase. Conclusions: The combination of RT and ZOL was more effective than either agent alone. Our results suggest that the administration of ZOL and irradiation in combination can offer maximal protection against DMBA-induced mammary precancerogenic changes.
Keywords: 7, 12-dimethylbenz[a] anthracene; breast cancer; zoledronic acid radiotherapy